On the choice of public pensions when income and life expectancy are correlated - Rainald Borck (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
The paper presents a model where public pensions are determined by majority voting. Voters differ by age and income. Moreover, life expectancy increases with income. Depending on the strength of the link between contributions and benefits, and the relationship between income and life expectancy, individually optimal tax rates may increase or decrease with income. If they decrease, high tax rates are supported by pensioners and poor workers. If they increase with income, the coalition for high tax rates consists of pensioners and rich workers. 'Ends against the middle' equilibria are also possible.
Keywords: H55; D72; 330; Voting; public pensions; life expectancy; Gesetzliche Rentenversicherung; Wahlverhalten; Einkommen; Sterblichkeit; Theorie